Detection of microbial colonization of the urinary tract of patients prior to secondary ureterorenoscopy is highly variable between different types of assessment: results of a prospective observational study. Issue 10 (26th November 2019) - Zumstein, Valentin; Betschart, Patrick; Buhmann, Matthias T.; Albrich, Werner C.; Nolte, Oliver; Güsewell, Sabine; Engeler, Daniel S.; Schmid, Hans-Peter; Ren, Qun; Abt, Dominik
Abstract: This study compares the findings of different detection methods for microorganisms in patients with ureteral stents undergoing secondary ureterorenoscopy including the use of a novel validated examination pipeline for biofilms on ureteral stents. Of the included 94 patients, 21.3% showed bacteriuria in preoperative urine cultures. Intraoperative urine culture showed bacteriuria in four (4.3%) of the patients. Stent biofilm cultures were positive in 12.9% and qPCR detected bacterial DNA in 18.1%. The findings of the different examinations were poorly correlated with each other. Detection of microorganisms in the urinary tract of patients with indwelling ureteral stents is highly dependent on timing (i.e. pre- vs intraoperative) and method of assessment. Preoperative routine urine cultures are not predictive for intraoperative urine- and stent culture. These results cast doubt on the clinical relevance of enterococcal species, staphylococci, and streptococci if identified preoperatively prior to stent removal. The timing of oral preoperative antibiotic prophylaxis might need to be reconsidered.